Iatrogenic air embolism. Issue 9 (10th June 2020) - Stringer, Bryan; Henry, Lucie; Foley, Raymond
Abstract: Air embolism should be treated promptly with high fraction of supplemental oxygen and repositioning to help facilitate reabsorption of the air bubble. Hyperbaric oxygen therapy should be given to those with severe disease. Abstract : Air embolism should be treated promptly with high fraction of supplemental oxygen and repositioning to help facilitate reabsorption of the air bubble. Hyperbaric oxygen therapy should be given to those with severe disease.